Implementation of Government Procurement Policy for Local MSMEs in the Context of Regional Economic Stimulus of Cirebon Regency - Halimatussa’diyah Halimatussa’diyah; Endang Sutrisno; Ipik Permana (Journal of Social Research, 2026)
This study was motivated by the low involvement of local MSMEs in the Government Goods/Services Procurement (PBJP) policy in Cirebon Regency, even though national regulations—particularly Presidential Regulation No. 12 of 2021—require a minimum allocation of 40% of government spending for MSMEs. This condition shows that the implementation of the policy has not functioned optimally as an instrument of local economic empowerment. This study aims to describe and analyze the implementation of PBJP for MSMEs and examine the construction of MSME empowerment mechanisms through this policy in the context of regional economic stimulus. The method used is a qualitative approach with a descriptive design through observation, in-depth interviews, and documentation involving the Cooperative and MSME Office apparatus and MSME actors. The results of the study show that the implementation of PBJP is still not optimal, as reflected in the low level of MSME participation (around 19% of 31,054 MSMEs), limitations in supporting regional regulations, lack of policy literacy, and uneven technical assistance. However, a high level of commitment was found among the implementing officials, and there were positive impacts on the MSMEs that had been involved, such as increased turnover and expansion of market networks. The study concludes that the effectiveness of PBJP as an SME empowerment instrument requires strengthening local regulations, increasing the capacity of implementing agencies and SMEs, and expanding access to information and assistance so that the stimulus can be maximized.